2015
DOI: 10.1128/jvi.02634-14
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of HIV-1 Infectivity through Endoplasmic Reticulum-Associated Degradation-Mediated Env Depletion

Abstract: During the HIV-1 replicative cycle, the gp160 envelope is processed in the secretory pathway to mature into the gp41 and gp120 subunits. Misfolded proteins located within the endoplasmic reticulum (ER) are proteasomally degraded through the ER-associated degradation (ERAD) pathway, a quality control system operating in this compartment. Here, we exploited the ERAD pathway to induce the degradation of gp160 during viral production, thus leading to the release of gp120-depleted viral particles.T he precursor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Therefore, we suggested that the UBE2N-associated ubiquitin transfer is induced by a signaling cascade leading to dysregulation of MIR101, MIR141, and MIR152. Additionally, we also found that ITPR1 is induced to regulate HIV-1 infectivity through endoplasmic reticulum-associated degradation [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggested that the UBE2N-associated ubiquitin transfer is induced by a signaling cascade leading to dysregulation of MIR101, MIR141, and MIR152. Additionally, we also found that ITPR1 is induced to regulate HIV-1 infectivity through endoplasmic reticulum-associated degradation [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…For VSV-G/Cas9 vesicle production, a 100-mm dish of confluent HEK293T cells was transfected with 15 μg of pxCas9, Gag-SpCas9, or pCDNA3-MinGag-Cas; 15 μg of the desired pUC-U6-sgRNA; and 3 μg of VSV-G plasmids using the polyethyleneimine (PEI) method. 50 Subsequent productions were performed in BSR-T7/5 cells using the conditions reported above, except for the pVAX-T7-sgRNA plasmid, which substituted pUC-U6-sgRNA for RNA guide expression. For Multi-VEsiCas deletion experiments, 7.5 μg of each pVAX-T7-sgRNA (sg EGFP5 and sg EGFPBi ) targeting EGFP was used for particle production.…”
Section: Methodsmentioning
confidence: 99%
“…Lentiviral particles were produced by seeding 4 × 10 6 HEK 293T or 293TR cells into a 10 cm dish, for lentiCRISPR or lentiSLiCES production, respectively. The day after the plates were transfected with 10 μg of each transfer vector together with 6.5 μg pCMV-deltaR8.91 packaging vector and 3.5 μg pMD2.G using the polyethylenimine (PEI) method 51 . After an overnight incubation, the medium was replaced with fresh complete DMEM and 48 h later the supernatant containing the viral particles was collected, spun down at 500 g for 5 min and filtered through a 0.45 μm PES filter.…”
Section: Methodsmentioning
confidence: 99%